The Perception of Emojis for Analyzing App Feedback - Scherr, Simon André; Polst, Svenja; Müller, Lisa; Holl, Konstantin; Elberzhager, Frank (International Journal of Interactive Mobile Technologies (iJIM), 2019)
When analyzing textual user feedback, the challenge today is that automation is only possible in a non-satisfactory way due to the limitations of understanding natural language. However, manual evaluation is not possible for products with a large amount of user feedback, as this is neither efficient nor effective. Internet texts are full of emojis. Emojis tell how a user feels about certain aspects of a product. We conducted a survey on the perception of emojis and used the results from 107 participants. The core result is that people perceive emojis in a very homogenous way regarding their sentiments and the emotions they represent This means that emojis give us a tool for analyzing the users’ perspectives on a product by looking at the emojis contained in their feedback.